CHLORBARTONITE, K6FE24S26(CL,S), A NEW MINERAL SPECIES FROM A HYDROTHERMAL VEIN IN THE KHIBINA MASSIF, KOLA PENINSULA, RUSSIA: DESCRIPTION AND CRYSTAL STRUCTURE - Yakovenchuk V.N.; Pakhomovsky Y.A.; Ivanyuk G.Yu.; Men'shikov Y.P.; Krivovichev S.V.; Burns P.C. (My University, 2003)
Chlorbartonite, ideally K6Fe24S26(Cl,S , is a new potassium iron sulfide chloride found as an accessory mineral in a microcline - pectolite - sodalite - aegirine vein within feldspathic urtite at Mount Koashva, Khibina massif, Kola Peninsula, Russia. The mineral occurs as roundish grains up to 2 cm across included in sodalite and natrolite crystals; it is associated with djerfisherite and rasvumite. Chlorbartonite is weakly magnetic, brittle, and has a conchoidal fracture. Cleavage and parting were not observed. Macroscopically, the mineral is opaque, brown-black, with a black streak and submetallic luster. In reflected light, it appears optically isotropic, yellowish brown, and without internal reflections; interpolated values of reflectance (R, %) at the standard wavelengths (nm) are: 10.8 (470), 13.5 (546), 15.1 (589), and 17.2 (650). The hardness VHN40 is 203-212, average 207 kg/mm2; the Mohs hardness is 4. The density is 3.70 g/cm3 (measured) and 3.65 g/cm3 (calculated). The electron-microprobe analysis of six grains gave, as an average composition: S 33.84, Cl 0.99, K 9.62, Fe 54.09, Co 0.04, Cu 0.57, total 99.15 wt.%. The empirical formula calculated on the basis of a total of 57 atoms is K6.08(Fe23.93Cu0.22Co0.01 = 2. The strongest eight lines in the X-ray powder-diffraction pattern [d in Å (I)(hkl)] are: 9.25(33)(101), 5.97(65)(112), 3.121(45)(312), 2.986(100)(224), 2.380(38)(332), 2.374(57)(316), 1.834(51)(440), and 1.830(82)(408). The crystal structure has been refined to an R1 of 0.020 (447 unique observed reflections with F0 ≥ 4σF0). The structure consists of a framework of the Fe8S14 clusters of eight edge-sharing FeS4 tetrahedra. The framework has large cavities occupied by CIK6 octahedra. As the name indicates, chlorbartonite is the Cl-dominant analogue of bartonite.
Keywords: chlorbartonite; new mineral species; bartonite; Khibina alkaline massif; Kola Peninsula; Russia